Spatio-temporal evolution and spatial patterns of traditional villages under multi-dimensional influential factors—a case study of Zhejiang Province, China - Guo, Yanlong; Wang, Longhao; Zhang, Ning; Huang, Jie (Frontiers in Earth Science, 2025)
IntroductionTraditional villages in China, with a history spanning over thousands of years, reflect significant socio-cultural evolutions and ecological adaptations.MethodsIn order to deeply explore the multidimensional factors affecting the layout and survival of villages, this study uses geographic data analysis, historical documentation, and ArcGIS 10.8 tools and applies spatial analysis methods such as kernel density, nearest neighbor index, disequilibrium index, and geodetic detector to characterise the layout of traditional villages and their influencing mechanisms in Zhejiang Province from the perspectives of spatial distribution, historical evolution, natural geography, and socio-economics. A systematic study was carried out.ResultsThe results of the study show that (1) the distribution of traditional villages in Zhejiang Province presents an unbalanced pattern of ‘double core and peripheral dispersion’, mainly concentrated in Lishui and Jinhua, with water resources and topographic conditions as the basis for aggregation; (2) the distribution of villages advances from northeast to southwest, reaching the peak of development in the Song, Ming, and Qing dynasties, reflecting the changes in national political policies This reflects the far-reaching influence of national political policy changes and ecological changes on village development; (3) Historical, geographic and social factors jointly play a role in the distribution of villages, in which geographic and natural factors such as elevation, precipitation, slope direction and water system dominate the siting and layout of villages.DiscussionThis study identifies the key influence mechanisms of factors such as elevation and water system on the distribution of villages, enriches the understanding of the spatial pattern and development mode of traditional Chinese settlements, and provides references for the sustainable development and cultural preservation of traditional settlements around the world.